Cashiers' contribution to organizations: A feminist perspective of accounting and countering - Clavijo, Nathalie; Dambrin, Claire (Contemporary Accounting Research, 2025)
This paper examines how a low‐skilled, gendered occupational group collectively counters representations of its contribution to organizational performance. We situate this process within the literature on counter accounts—alternative representations designed to rectify perceived harms or injustices. Our study focuses on cashiers, referred to as “checkout hostesses” in their organization's gendered terminology, in the highly masculine building supplies sector. Drawing on a feminist theorization of counter accounts and a 1‐year ethnography at two levels (in a store and in a cashiers' working group), we show that cashiers produce three counter accounts: (1) a vocational qualification that highlights their accounting and selling skills, (2) a reframing of their customer credit activities as a contribution to sales, and (3) a quantification of their selling activity in a dashboard tracking sales at the checkout. These counter accounts challenge patriarchal social structures that frame their job as a low‐status “woman's job,” objectify them, and overshadow their contribution to organizational performance. We advance the concept of counter accounts from the inside, showing that they do not merely denounce oppression but also repurpose stereotypical gender and class norms as resources for collective empowerment. We also emphasize how internal organizational support fosters occupational groups' awareness of their agency. Finally, we argue that the potential and limitations of counter accounts must be assessed from the perspective of the vulnerable group itself, broadening their understanding as emancipatory tools produced for the “other” by the “other.”